Untersuchungen über die Lebensweise und Entwicklung der Maulwurfsgrille (Gryllotalpa vulgaris Latr.) im Lande Brandenburg. - Hahn, E. (Contributions to Entomology = Beiträge zur Entomologie, 1958)
There are communicated the results of studies on biology, development, and distribution of the mole-cricket (Gryllotalpa vulgaris Latr.) in Brandenburg and discussed new interesting facts of seasonal appearance, hibernation, and larval development with special reference to oviposition, nidification, and number of moultings. A biologic race of Gryllotalpa vulgaris Latr. with a remarkable behaviour was found.